"Brain Drain/Gain interno" uma análise da fuga de cérebros na mesorregião geográfica Oeste do Paraná - Mezzon, Júlio Cezar Streeling (2021)
Brain Drain or brain drain is widely studied around the world with the aim of measuring the amount and impact of the mobility of more qualified personnel between underdeveloped countries in developed countries. The ease of admission to higher education courses experienced in Brazil, after the 2000s, was also present in western Paraná State. Moreover, because it is a relatively new region, the area showed dynamism in the evolution of the socioeconomic variables selected between 2000 and 2010, which had a result very close to or higher than the growth presented by the state. With this work, was expected a study focused on displacement between municipalities within a mesoregion is expected. Therefore, the objective of this dissertation is to measure and analyze socioeconomic factors of the 50 municipalities of the Western Geographic Mesoregion of Paraná between 2000 and 2010, caused and/or causing Brain Drain/Gain in these municipalities. Therefore, qualitative and quantitative methodologies are used to understand the migratory flows of these professionals, in order to present an overview of the issue from the graphical analysis of migratory flows; the composition of an adapted Brain Drain/Gain index – IBDGa and its comparison with socioeconomic employment variables; income; urbanization and quality of life. Thus, it was identified that qualified migrants who relocated spatially until 2010 to and from municipalities in western Paraná State were influenced by the combination of dand factors, such as: employment; quality of life; urbanization and income,compared between the city of origin and the city of destination. Moreover, it was found that the circulation of brains in western Paraná State was markedby,until 2010, by migratory movements of short distance. However, in the inflows of this human capital from the state, it was possible to identify that the capital increase that occurred no Oeste until 2010, was not mostly formed in the mesoregion. Analyzing the process of spatial redistribution of the graduated population of the West, it was observed that Cascavel and Toledo presented migratory currents and countercurrents among themselves. After all, the largest number of cascavelenses migrants headed to Toledo by 2010, while the preferred destination for Toledenese brains was Cascavel. Of the five largest attractors of oestino human capital until 2010, three of them are municipalities where Unioeste. While Medianeira has owned a campus of the Technological University of Paraná - UTFPR since 1990 and Palotina has a campus of the Federal University of Paraná - UFPR. This indicates that migration may have occurred in the individual's search to acquire human capital.